Scale-up of reverse electrodialysis for energy generation from high concentration salinity gradients - Hulme, Anna; Davey, Christopher J.; Tyrrel, Sean; Pidou, Marc; McAdam, Ewan (Cranfield University, 2021)
Underlying data for manuscript.
Keywords: 'Reverse electrodialysis'; 'closed-loop'; 'recycle'; 'battery'; 'thermal-to-electric'; 'cell pair'; 'salinity gradient energy'; 'Chemical Engineering Design'; 'Renewable Power and Energy Systems Engineering (excl. Solar Cells)'; 'Membrane and Separation Technologies'